The Role of Lithuanian Heritage Language Schools in Cultural Identity and Language Learning: Perceptions of Parents and Teachers - Daiva Jakavonytė-Staškuvienė; Justina Ardzijauskienė (Social Sciences)
This study aims to examine how children growing up in Norway develop Lithuanian heritage language skills and maintain their Lithuanian identity based on the perceptions of parents and teachers. Theoretical Basis: The study is grounded in social identity theory, which helps to understand how personal and social identity is formed and transformed through interactions in various social environments. Methodology: A case study strategy was chosen, allowing the phenomenon to be interpreted in different environments and perspectives. The study describes the environments and contexts of three Lithuanian heritage language schools operating in Norway, as the participating teachers (n = 5) and parents (n = 8) are from these schools. The results showed that in Lithuanian cultural schools, which operate every other Saturday, the spoken Lithuanian language is developed, children are introduced to Lithuanian history, traditions, and culture, and Lithuanian holidays are celebrated. However, parents have different expectations when sending their children to these Lithuanian heritage language schools; some are satisfied with the spoken Lithuanian language, while others want deeper learning of Lithuanian writing so their children can take the Lithuanian language exam.